Linguistic Transfer: Case Study - Ramírez Osorio, José Fernando; Ríos Martínez, Jhon Fredy; Ramírez Osorio, José Fernando; Ríos Martínez, Jhon Fredy; Ramírez Osorio, José Fernando; Ríos Martínez, Jhon Fredy (Corporación Universitaria Americana, 2023)
Introduction: This article is part of a descriptive research developed between 2019 and 2022 with the students of the Modern Languages ​​Program of the University of Caldas, Colombia. It deals with the presence of other languages in a base language (language in use) ​​at the scriptural level. Objective: The main objective of the research is to explain the phenomenon of transfer in light of the syntactic, semantic and pragmatic levels and to be able to determine whether or not it is an ungrammaticality, as well as the reasons why this phenomenon occurs in language learning. Methodology: We made use of a method based on a series of interviews with foreign language teachers in Colombia and some surveys of language students. Results: Then a linguistic analysis was applied to a series of written texts where transfer was evident. Conclusion: Finally, it was concluded that the phenomena of transfer and interference do not occur due to the hierarchy of acquisition over learning, nor due to the kinship of languages ​​or similarities between them, but because of the affinities derived from the greater use or contact with the linguistic code.